Progressive ventilation inhomogeneity in infants with cystic fibrosis after pulmonary infection - Simpson, S.; Ranganathan, S.; Park, J.; Turkovic, L.; Robins-Browne, R.; Skoric, B.; Ramsey, K.; Rosenow, T.; Banton, G.; Berry, L.; Stick, S.; Hall, Graham (European Respiratory Society, 2015)
Measures of ventilation distribution are promising for monitoring early lung disease in cystic fibrosis (CF). This study describes the cross-sectional and longitudinal impacts of pulmonary inflammation and infection on ventilation homogeneity in infants with CF. Infants diagnosed with CF underwent multiple breath washout (MBW) testing and bronchoalveolar lavage at three time points during the first 2 years of life. Measures were obtained for 108 infants on 156 occasions. Infants with a significant pulmonary infection at the time of MBW showed increases in lung clearance index (LCI) of 0.400 units (95% CI 0.150–0.648; p=0.002). The impact was long lasting, with previous pulmonary infection leading to increased ventilation inhomogeneity over time compared to those who remained free of infection (p<0.05). Infection with Haemophilus influenzae was particularly detrimental to the longitudinal lung function in young children with CF where LCI was increased by 1.069 units for each year of life (95% CI 0.484–1.612; p<0.001). Pulmonary infection during the first year of life is detrimental to later lung function. Therefore, strategies aimed at prevention, surveillance and eradication of pulmonary pathogens are paramount to preserve lung function in infants with CF.